Investor protection and the demand for equity - Mariassunta Giannetti; Yrjö Koskinen (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
Anecdotal evidence suggests that investor protection affects the demand for equity, but existing theories emphasize only the effect of investor protection on the supply of equity. We build a model showing that the demand for equity is important in explaining financial development. If the level of investor protection is low, wealthy investors have an incentive to become controlling shareholders and pay a high price for their stocks, because they can earn additional benefits by expropriating outside shareholders. As a consequence of lower expected returns both domestic and foreign portfolio investors have a disincentive to hold stocks. The model implies that differences in stock market participation rates across countries and the pervasiveness of home equity bias depend on the degree of investor protection. Additionally, we uncover a good country bias in investment decisions as portfolio investors from countries with low level of investor protection hold relatively more foreign equity. We provide novel international evidence on stock market participation rates, and on holdings of domestic and foreign stocks consistent with the predictions of the model.
Keywords: F21; G11; G32; G38; 330; Home Equity Bias; Portfolio Choice; Limited Participation; Investor Protection; Private Benefits of Control